An update on the hazard of and exposure to diethyl hexyl phthalate (DEHP) alternatives used in medical devices. (13th September 2020) - Den Braver-Sewradj, Shalenie P.; Piersma, Aldert; Hessel, Ellen V. S.
Abstract: The use of the plasticizer diethyl hexyl phthalate (DEHP) in PVC medical devices is being questioned due to its potential reprotoxic effects in patients exposed as a result from migration from the device. This article reviews new information on migration and toxicity data of eleven alternative plasticizers that have previously been evaluated by the Danish EPA and the EU SCENIHR (Scientific Committee on Emerging and Newly Identified Health Risks). The new toxicity data did not justify the reconsideration of the critical NOAELs as established by SCENIHR and Danish EPA. The dataset on oral toxicity studies is rather complete for most substances; however, in particular for reproductive toxicity and endocrine disruption, data gaps still exist for many alternatives. Toxicity data on intravenous exposure are lacking and these are essential to conclude on hazard characteristics of alternatives that are poorly absorbed via the oral exposure route. Migration data are emerging for a few alternatives but still sparse for the majority of the alternatives. Taking all data on migration and toxicity in consideration, 1, 2-cyclohexanedicarboxylic acid, diisononylester (DINCH), and tris(2-ethylhexyl)benzene-1, 2, 4-tricarboxylate display a more favorable profile compared to DEHP. For these promising alternatives, a risk assessment for use in medical devices should be conducted. As a next step, we recommend the (further) generation of relevant migration data and, where needed, relevant toxicity data for the alternative substances, in order to be able to conduct a benefit-risk analysis of DEHP and the alternatives as obligatory in the new European Union Medical Device Regulation.